THE INFLUENCE OF TAX MORALE, PUBLIC GOVERNANCE QUALITY, MEDIA NEGATIVITY BIAS ON TAX COMPLIANCE OF INDIVIDUAL TAXPAYERS WITH TRUST AS A MODERATION VARIABLE (Study on WPOP in Salatiga City) - Hasna Maharani (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to analyze the effects of tax morale, public governance quality, and medianegativity bias on individual taxpayer compliance, with trust serving as a moderating variable. Aquantitative research design was employed, with data collected through both offline and onlinequestionnaire surveys. Using a non-random sampling technique, a total of 135 respondents wereobtained. The collected data were analyzed using SPSS version 25. The finding indicate that taxmorale and media negativity bias have a positive and significant impact on tax compliance. Incontrast, public governance quality shows a negative but insignificant effect on tax compliance.Furthermore, trust is found to moderate the relationship between tax morale and tax complianceas well as the relationship between media negativity bias and tax compliance. However, trust doesnot moderate the relationship between public governance quality and tax compliance.